Cell-free synthesis of simian virus 40 T-antigens. - Paucha, E (1978)
Polyacrylamide gel electrophoresis and tryptic peptide fingerprint analysis of the proteins made in a cell-free system derived from L-cells and immunoprecipitated with simian virus 40 (SV40) anti-T serum demonstrated that both SV40 large-T and small-T antigens are synthesized in vitro in response to mRNA isolated from productively infected CV1 CELLS. Sucrose density centrifugation in gradients containing 85% formamide showed that the mRNA's for both forms of T-antigen sediment at about 17.5S, with the mRNA for small-t sedimenting marginally, but reproducibly, ahead of the mRNA for large-T. Hybridization experiments using restriction endonuclease fragments Hae III-E and Hind II/III-B showed that all fractions active in the cell-free synthesis of both forms of T-antigen hybridized equally to both fragments. This suggests that the mRNA's for SV40 T-antigens are at least partly virus coded and that the bulk of the early SV40 mRNA contains sequence information from both ends of the early region. The data are consistent with the suggestion that the large-T mRNA is spliced. SV40 complementary RNA (the product of transcription of SV40 DNA using Escherichia coli RNA polymerase) was also translated in the L-cell system and gave two families of polypeptides which specifically immunoprecipitate with anti-T serum. One family (the small-t family) includes a polypeptide indistinguishable by gel electrophoresis and tryptic peptide fingerprinting from small-t isolated from cells. The other family (the 60K family) has a major component with molecular weight approximately 60,000 and includes other polypeptides with molecular weights ranging from approximately 14,000 to about 70,000. The 60K family has petides in common with large-T but not with small-T. Together, the peptides of the small-t and 60K families account for virtually all of the methionine peptides of SV40 large-T. We conclude from these results (i) that small-t is probably entirely, and large-T at least predominantly, virus coded; (ii) that the small-t and 60K families represent the translation products of two different portions of the early region of SV40 DNA (approximately 0.65 to 0.55 map units and 0.54 to 0.17 map units); and (iii) that although most, if not all, of the large-T and small-t peptides are present in the cell-free product, some feature of sequence arrangement of SV40 complementary RNA prevents the translation of full-length large-T and results instead in the synthesis of fragments. We suggest that the absence of a splice in the complementary RNA is responsible for this result.